(untitled) (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Shaykhul Islam IbnTaymiyya (r) was one of the mentionable characters among the Muslims scholars in medieval period, who have contributed much in their respective field towards science, knowledge and civilization. His contribution to all major branches of Islamic knowledge was of great significance. Especially, his speeches, writings, Fatwas and various activities were very much effective for his contemporary ages as well as for the current post-Modern world. His rulings on different issues of Christianity were played a significant role for decision for Muslimsof that time. These have also significant role in the mutual relationship between Muslims and Christians of our time. As a result, a great wave of research to work on IbnTaymiyya’s thoughts and writings has been flourished in everywhere in the east as well as in the west. This article is the result of this continuous research process. It is a neutral attempt to present IbnTaymiyya’s Fatwas related to Christianity, so that the nature of Islamic directions on Muslim-Christian relations would be clearer for the Muslims. সারসংক্ষেপ : মধ্যযুগের মুসলিম জ্ঞান-বিজ্ঞান ও সভ্যতায় যেসব মনীষী উল্লেখযোগ্য অবদান রেখেছেন তাদের অন্যতম হলেন শায়খুল ইসলাম ইমাম ইবন তাইমিয়া রহ. (১২৬৩-১৩২৮খ্রি.)। ইসলামী জ্ঞানের বিভিন্ন শাখায় তাঁর রচনাবলি ও অবদান অবিস্মরণীয়। বিশেষ করে খ্রিস্টবাদ সম্পর্কে তাঁর বক্তব্য, ফাতওয়া, লেখা ও কর্মকা- তৎকালীন মুসলিমদের জন্য সংশ্লিষ্ট জ্ঞানের অন্যতম উৎস হিসেবে বিবেচিত। এমনকি বর্তমান উত্তরাধুনিক সময়েও সেসব ফাতওয়া ও লেখালেখি নিয়ে ব্যাপক আলোচনা-পর্যালোচনা রয়েছে। খ্রিস্টবাদ সম্পর্কিত বিভিন্ন মাস’আলায় তাঁর প্রদত্ত ফাতওয়া সে সময় মুসলিমদের সিদ্ধান্ত গ্রহণে গুরুত্বপূর্ণ ভূমিকা রেখেছে। বর্তমান সময়ে মুসলিম ও খ্রিস্টানদের পারস্পরিক সম্পর্কের ক্ষেত্রেও এসব ফাতওয়া পর্যালোচনার দাবি রাখে। এজন্য প্রাচ্যের পাশাপাশি পাশ্চাত্যেও ইবন তাইমিয়া রহ.-এর চিন্তাধারা ও কর্মের পুঙ্খানুপুঙ্খ বিশ্লেষণ নতুন মাত্রা লাভ করেছে। আলোচ্য প্রবন্ধ এরই ধারাবাহিকতার ফলস্বরূপ। এতে খ্রিস্টবাদ সম্পর্কিত ইবন তাইমিয়া রহ. প্রদত্ত ফাতওয়াসমূহের নিরপেক্ষ উপস্থাপন করা হয়েছে, যাতে বর্তমান সময়ে মুসলিম-খ্রিস্টান সম্পর্কের ইসলামী নির্দেশনার স্বরূপ সহজে প্রতিভাত হয়ে ওঠে।